35‐2: Influence of Low Ground Mass and Moisture Touch in On‐Cell Touch with Foldable AMOLED. Issue 1 (25th September 2020) - Huang, Shih-Hsuan; Su, Wei-Jen; Ko, Chien-Ming; Hsu, Heng-Chia; Lin, Hong-Shen
Abstract : In this work, we overcome two TP sensing issue, including low ground mass and moisture touch error by changing sensor geometry and area while we were trying to reduce foldable on‐cell touch (FOCT) thickness and the design was successfully been demonstrated with high touch performance.